P135: TriagED: A serious game for mass casualty triage and field disaster management. (May 2019) - Wallner, C.; Sneath, P.; Morgan, K.; Chan, T.
Abstract : Innovation Concept : Mass Casualty Incidents (MCI) are complex events that most paramedics encounter only a few times in their careers. Triaging and managing multiple patients during an incident requires different skills than typically practiced by prehospital providers. Simulation and drills can provide an opportunity to practice those skills, but are costly and resource intensive while only allowing a few providers to be in a triage or leadership role. It is important to find engaging and less expensive methods for teaching MCI triage and initial scene management.Methods : The authors have developed and are testing a card game based on the previously published GridlockED board game. The game was developed utilizing an iterative process previously described. This game was tested with paramedics as well as other emergency medicine learners to determine usability, engagement, fidelity, as well as usefulness in teaching MCI triage and patient-flow concepts.Curriculum, Tool or Material : The card game provides a focused learning experience to allow providers to practice initial triage of multiple injured patients as well as manage patient flow from the scene to area hospitals when faced with limited prehospital resources and capabilities. Players work together in various simulated scenarios to correctly triage injured patients and send them to the correct healthcare facility.Conclusion : Serious gaming has gained momentum in medical education. Developing novel curriculae around low frequency, high stakes situations using a game like TriagED may hold the key to ensure prehospital care providers are trained for these incidents. In the future, games which integrate an element of Incident Command or receiving hosptials (e.g. full integration with GridlockED game) may help to further explore the relationship between scene management and patient flow within receiving hospitals.